Strategi Pemasaran Produk Indosat M3 di Kota Kediri Berdasarkan Analisis SWOT - Ana Komari (Universitas 17 Agustus 1945 Surabaya, 2016)
The business world of telecommunications is now a full decade with the changes thatare filled with newcomers in the business world of telecommunications. The changes andupheavals are not just fast, unpredictable and complex, but also contradictory and couldlead to a crisis (Pierce & Robinson, 1994). To respond to these changes companies need tofundamentally rethink their strategy, structure, performance in order to have the ability tocompete in the increasingly fierce competition conditions. The company is required tocontinuously adjust its strategic planning related to the company business environment sothat the chosen strategy is always appropriate.In order to find the appropriate marketing strategy formulation then it is needed efforts toidentify the strengths, weaknesses, opportunities and threats faced by the company. Forthose reasons, this study was held which focused on the determination efforts of themarketing strategy that appropriate with the company condition in the middle ofcompetition. Research conducted in Indosat M3 in particular on its Smart product used aqualitative method by using respondent of employees who have an understanding of themarket conditions that amounted to 15 people. Data collection tool used was a structuredquestionnaire with closed-type questions. The results of this study indicated that thestrategy formulation suggested for Indosat M3 Smart is an investment strategy byemphasizing on distribution and pricing strata such as make empowering potential outlets,cooperate with Bank Mandiri and BCA, as well as the incentives system for the interestingchanneling. Thus, Indosat M3 Smart products can feature their competitive advantage ifcompared to other similar competitors.Keywords: IM3, Telecommunications, Marketing Strategy, SWOT Analysis.